Sporulation capability and amylosome conservation among diverse human colonic and rumen isolates of the keystone starch‐degrader Ruminococcus bromii. (7th December 2017) - Mukhopadhya, Indrani; Moraïs, Sarah; Laverde‐Gomez, Jenny; Sheridan, Paul O.; Walker, Alan W.; Kelly, William; Klieve, Athol V.; Ouwerkerk, Diane; Duncan, Sylvia H.; Louis, Petra; Koropatkin, Nicole; Cockburn, Darrell; et al.
Summary: Ruminococcus bromii is a dominant member of the human colonic microbiota that plays a 'keystone' role in degrading dietary resistant starch. Recent evidence from one strain has uncovered a unique cell surface 'amylosome' complex that organizes starch‐degrading enzymes. New genome analysis presented here reveals further features of this complex and shows remarkable conservation of amylosome components between human colonic strains from three different continents and a R. bromii strain from the rumen of Australian cattle. These R. bromii strains encode a narrow spectrum of carbohydrate active enzymes (CAZymes) that reflect extreme specialization in starch utilization. Starch hydrolysis products are taken up mainly as oligosaccharides, with only one strain able to grow on glucose. The human strains, but not the rumen strain, also possess transporters that allow growth on galactose and fructose. R. bromii strains possess a full complement of sporulation and spore germination genes and we demonstrate the ability to form spores that survive exposure to air. Spore formation is likely to be a critical factor in the ecology of this nutritionally highly specialized bacterium, which was previously regarded as 'non‐sporing', helping to explain its widespread occurrence in the gut microbiota through the ability to transmit between hosts.